POST-CONSERVATION EVALUATION (PCE) ON HISTORIC BUILDINGS: AUTHENTICITY OF ADAPTIVE REUSE MUSEUMS IN GEORGE TOWN, UNESCO WORLD HERITAGE SITE - Abdul Aziz, Muhammad Firzan (PLANNING MALAYSIA, 2021)
Adaptive reuse has apparently become a favourable means of built heritage conservation in the UNESCO World Heritage Site (WHS) of Melaka and George Town. In most cases, adaptive reuse implementations inflict conflicting demands to historic buildings in terms of meeting new functional needs and retaining physical authenticity. Inappropriate implementation of adaptive reuse for historic buildings within WHS may result in the violation of Outstanding Universal Values (OUVs). The purpose of this study is to determine the authenticity condition of historic buildings on their post-conservation phase, after adaptive reuse implementation. Five historic buildings namely the Penang State Museum (PSM), Made in Penang Interactive Museum (MIPIM), Sun Yat Sen Museum (SYSM), Batik Painting Museum (BPM) and Dark Mansion-3D Glow in the Dark Museum (DM) were evaluated through field observation. In accommodating the museum function, three elements were found to be intervened inappropriately at these buildings namely the internal wall, windows, and building services. The findings of this evaluative study can be useful to technical review panels appointed by heritage authorities, in scrutinising heritage impact assessment (HIA) reports and evaluating future proposals concerning adaptive reuse projects of historic buildings within WHS.